Servant Leadership dan Disiplin Kerja: Antara Efek Parsial dan Simultan pada Kinerja Karyawan - M.I.Adhisti.P.D; J. Sabas Setyohadi; Sumaryati. T (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the effect of servant leadership and work discipline on employee performance partially and simultaneously. The research approach is quantitative with a survey method. Collecting data using a questionnaire that was compiled based on the development of indicators for each variable. The sampling technique used a saturated sample technique of 50 employees. Data analysis techniques used are normality test, correlation, coefficient of determination, linear regression, and hypothesis testing. The calculation of the partial test using the t test showed that there was a significant influence of servant leadership on employee performance and there was a significant effect of work discipline on employee performance. The results of the simultaneous test using the F test showed that servant leadership and work discipline simultaneously had a significant effect on employee performance.